Starch/PVA-based nanocomposites reinforced with bamboo nanofibrils - Guimarães Jr, Mario; et. al. (2015)
This work aimed to evaluate the effect of including different concentrations of bamboo nanofibrils on physical, mechanical, morphological and structural properties of nanocomposites from cassava starch and polyvinyl alcohol (PVA). Nanocomposites were prepared with blends of starch/PVA and nanofibrils of bamboo. Chemical pre-treatments and mechanical defibrillation were used to obtain the nanofibrils. The mixture containing 3% of starch and 4% of PVA in the proportion of 20/80 (starch/PVA) were chosen after preliminary testing. Atomic force microscopy (AFM) and transmission electronic microscopy (TEM) were used to characterize the bamboo nanofibrils. Microstructure of the nanocomposites was evaluated using scanning electron microscopy (SEM) and X-ray diffractrometry (XRD). Physical and mechanical properties were also evaluated. Results showed that pre-chemical treatments increased the content of the alpha-cellulose in bleached pulp by approximately 112% in relation to the native fiber. Increasing the number of passages through the defibrillator reduced the average diameter of the bamboo nanofibrils (from 82 ± 29 nm to 10 ± 6 nm). Addition of 6.5% nanofibrils improved the tensile strength and elongation at the break of the nanocomposite by 24 and 51%, respectively, but reduced the tensile modulus by 40% in relation to control (unreinforced) blend. Nanofibrils decreased the transparency of the nanocomposite films. The water vapor permeability and water solubility of the nanocomposite containing high contents of nanofibrils decreased up to 20% and 30%, respectively, in relation to the control blend. © 2015 Elsevier B.V. All rights reserved.